The Linear Matching Method applied to composite materials: A micromechanical approach - Barrera, O; Cocks, A; Ponter, A (2011)
The paper considers a Direct Method for the evaluation of the maximum load corresponding to pre-assigned limits on the non-linear behaviour of the matrix and fibres in a laminate structure. This is achieved by combining a consistent micro-macro model for linear behaviour with an extension of the Linear Matching Method (LMM), previously extensively applied to Direct Methods in plasticity. The method is developed with assumptions that allow the methodology to be displayed in its simplest form. Applications to examples of laminate elements and a laminate plate containing a hole are described, assuming a matrix with a limit on ductility. © 2010.